REVENUE ACT OF 1954–SIGNIFICANT ACCOUNTING CHANGES. - Cohen, Albert H. (The Accounting Review, 1954)
The article focuses on accounting changes brought about by the Revenue Act of 1954. Though the general rule for accounting methods under the Internal Revenue Code of 1954, as set forth in section 446, is substantially the same as the general rule under the Internal Revenue Code of 1939, there are a number of specific types of accounting problems which are singled out for special treatment in the new Code. For the most part, these special provisions represent an effort on the part of the lawmakers to bring tax accounting into closer accord with generally accepted accounting principles. Under the various revenue acts prior to 1939 and under the Internal Revenue Code of 1939, there were many differences between the accounting for certain transactions for tax purposes and for commercial purposes. Some of the major differences could be explained on the grounds of public policy, as in the case of the peculiar treatment of capital gains and losses and in the allowance of percentage depletion, to name only two. Others could be said to result from the necessity of determining taxable net income rather than business net income, as in the case of the allowances for expenses of a purely personal nature and the credits for personal exemptions.